Moral Branding and Ethical Consumption: Bibliometric Trends in Value-Based Marketing Approaches - Judijanto, Loso; Nurwanto, Novi; Saununu, Siska Jeanete (West Science Social and Humanities Studies, 2025)
This study examines the conceptual framework and thematic progression of research on moral branding and ethical consumerism by a bibliometric analysis of publications indexed in Scopus from 2000 to 2025. The study employs VOSviewer and Biblioshiny to delineate major clusters pertaining to branding, consumer behavior, sustainability, and digital ethics. Results demonstrate a shift from initial psychological and behavioral models to interdisciplinary frameworks that incorporate sustainability and value-driven marketing. The United Kingdom and the United States appear as primary providers, while collaborations from Asia and Europe are becoming more prominent. The research offers theoretical and managerial insights for incorporating moral authenticity, sustainability, and consumer trust into branding initiatives. It additionally suggests a Value–Ethics–Sustainability paradigm as a conceptual framework to direct future inquiries in ethical marketing.